Paul Maenz Köln Ausstellungen : Herbst 1986 - Sommer 1987. - Paul Maenz, Köln (Köln : Paul Maenz, 1987)
Bickerton, Ashley ; Bömmels, Peter ; Dahn, Walter ; Dokoupil, Jiri Georg ; Knap, Jan ; Koons, Jeff ; Posenenske, Charlotte ; Salvo ; Schuyff, Peter ; Steinbach, Haim ; Taaffe, Philip ; Vaisman, Meyer
Duits & Engels
boek